2010
DOI: 10.1093/cvr/cvq149
|View full text |Cite
|
Sign up to set email alerts
|

Improved heart function follows enhanced inflammatory cell recruitment and angiogenesis in 11βHSD1-deficient mice post-MI

Abstract: Increased vessel density in healing infarcts of mice deficient in 11(-/-)HSD1 follows recruitment of pro-reparative macrophages and increased pro-angiogenic signalling. Mature infarcts show less thinning and cardiac function is improved relative to wild-type mice, suggesting that 11βHSD1 may be a novel therapeutic target after MI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
76
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(93 citation statements)
references
References 56 publications
15
76
1
Order By: Relevance
“…However, the peritonitis was actually found to resolve at the same rate as the wildtype animals (44). Similarly, cardiac function was much better preserved in 11β-HSD1 knockout mice following myocardial infarction, despite initially having comparatively higher levels of local inflammation (45,46). Although these studies imply that loss of 11β-HSD1 may not have an adverse impact on an acute inflammatory response, a study using a mouse model of arthritis and carrageenaninduced pleurisy found 11β-HSD1-deficiency to result in the converse (47).…”
Section: European Journal Of Endocrinologymentioning
confidence: 86%
“…However, the peritonitis was actually found to resolve at the same rate as the wildtype animals (44). Similarly, cardiac function was much better preserved in 11β-HSD1 knockout mice following myocardial infarction, despite initially having comparatively higher levels of local inflammation (45,46). Although these studies imply that loss of 11β-HSD1 may not have an adverse impact on an acute inflammatory response, a study using a mouse model of arthritis and carrageenaninduced pleurisy found 11β-HSD1-deficiency to result in the converse (47).…”
Section: European Journal Of Endocrinologymentioning
confidence: 86%
“…Increased recruitment of neutrophils and macrophages within the first days after MI has recently been shown to lead to enhanced neovascularization, a reduction in infarct thinning, and functional improvement in 11␤HSD1-deficient mice. 46 The improved collagen structural organization in the infarct scar in MR MLCCre mice may also be of particular importance, most likely secondary to MMP downregulation. 21 Disorganized collagen matrix renders the scar less resistant to distention during overload and predisposes to thinning and dilatation of the infarcted wall, paving the way for progressive global ventricular dilation, LV dysfunction, and heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…As a recently published phase II trial shows, these cognitive benefits may not extend into groups with more advanced dementia caused by Alzheimer's disease [91], but should now be tested using drugs targeted to access 11βHSD1 in the central nervous system and in patients with mild cognitive impairment and/or vascular dementia. 11βHSD1 deficiency is also associated with enhanced angiogenesis in ischaemic tissues, resulting, for example, in improved left ventricular function following myocardial infarction in mice and potentially improving wound healing [97,98], a common problem in diabetes. Increased 11βHSD1 activity in ageing human fibroblasts leads to skin ageing and impaired wound healing, and topical application of an 11βHSD1 inhibitor improves wound healing in humans [99,100].…”
Section: Outstanding Challengesmentioning
confidence: 99%